2019
DOI: 10.1101/829465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recurrent loss ofabaA, a master regulator of asexual development in filamentous fungi, correlates with changes in genomic and morphological traits

Abstract: Author Summary 46Fungi exhibit tremendous variation in their asexual fruiting bodies. For example, whereas some 47 fungi form complex fruiting bodies whose tips repeatedly generate and release spores, others 48 produce single spores in the absence of a specialized structure. To gain insights into the 49 molecular differences that underpin fungal asexual fruiting body diversity, we examined the 50 genomes of hundreds of filamentous fungi for the presence of abaA, a master regulatory gene 51 previously shown to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…2 and 5 ). BrlA and AbaA are two key DNA-binding transcriptional factors in regulation of asexual proliferation, in which BrlA initiates the program, and AbaA activates the development of the phialides in conidiophores (the asexual fruiting bodies) of filamentous fungi (Mead et al 2020 ; Sewall 1994 ). By deletion of PHD and Atrophin-1 domain, it was found that, similar to Δ cti6 , the fungal colony size, mycelial density and conidiation state of PHD domain deletion strain ( cti6 ΔPHD ) on both PDA media and crop kernels were significantly restrained compared to the Ctrl fungal strain, but Atrophin-1 domain was only involved in the sporulation of the fungus (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 5 ). BrlA and AbaA are two key DNA-binding transcriptional factors in regulation of asexual proliferation, in which BrlA initiates the program, and AbaA activates the development of the phialides in conidiophores (the asexual fruiting bodies) of filamentous fungi (Mead et al 2020 ; Sewall 1994 ). By deletion of PHD and Atrophin-1 domain, it was found that, similar to Δ cti6 , the fungal colony size, mycelial density and conidiation state of PHD domain deletion strain ( cti6 ΔPHD ) on both PDA media and crop kernels were significantly restrained compared to the Ctrl fungal strain, but Atrophin-1 domain was only involved in the sporulation of the fungus (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge thus gained can, of course, be extended to other fungal systems. Recently, new experimental approaches have been developed, focused on the expression of genes encoding regulators of A. nidulans asexual reproduction with the aim of modifying developmental patterns of species such as Monascus ruber or Histoplasma capsulatum (Ojeda-López et al 2018;Mead et al 2020). Although the trials were unable to trigger major morphological changes, they paved the way for the establishment of simple and reliable approaches for the experimental study of GRN rewiring and its consequences on organism evolution.…”
Section: How Grns Evolve and What Can Fungi Teach Us About The Processmentioning
confidence: 99%